A solitary palatal mass - T Manigandan; V Shivakumar; B Karthika; S C Selvamuthukumar; Nalini Aswath (Wolters Kluwer Medknow Publications, 2012)
Myoepithelioma is a rare benign neoplasm of major and minor salivary glands, composed almost exclusively of sheets, islands or cords of cells with myoepitheliomal differentiation. Myoepithelioma represents 15% of all salivary glands neoplasm, most commonly occurs in parotid gland. Here, we report a rare case of myoepithelioma of hard palate.